Flattening of Bond Yield Curves for Long Maturities - Livingston, Miles; Jain, Suresh (Journal of Finance, 1982)
The paper presents a theoretical proof that flattening of yield curves for par bonds is inevitable for long maturities. This proof implies that behavioral explanations of flattening are unnecessary. The proof also implies that the use of yields to maturity of couponbearing bonds to estimate the true term structure (as well as forward rates) for long maturities has potentially infinite bias, suggesting that a greater effort should be made to directly estimate the true term structure in empirical work.